Application of Bankruptcy Prediction Models for Real Estate Companies Listed on The Indonesia Stock Exchange (IDX) - Iwan Nurfahrudin; Raden Aswin Rahadi (CV. Ridwan Publisher, 2021)
A company that is built not only could make a profit, but also definitely has the risk of bankruptcy. This research aims to measure and analyze the potential for bankruptcy from the analysis of several methods compared to the reality in the field. The sample used in this study were several real estate companies in Indonesia which were listed on the Indonesia Stock Exchange from 2017 to 2019. The methods used in predicting company bankruptcy in the property sector are the Altman Z-score, Altman Revised Z-score, and Springate methods. Based on the research results, companies that tend to be at risk of bankruptcy according to the three models are APLN, CTRA, DART, EMDE, PPRO, and SMRA with Altman Z-score < 1.8, Altman Revised Z’-score < 1.23, and Springate S-score < 0.862.